An introduction to sociology - Browne, Ken , 1951- (Polity Press, 2011)
New edition of a highly successful textbook invaluable to anyone taking an introductory sociology course, especially GCSE and Access courses. * Thoroughly revised and updated, the 4th edition provides comprehensive coverage of a wide range of topics, including those specified by the main GCSE exam boards